Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Guru Pada SMA Negeri 1 Karawang - Agustin, Ika; Tuhagana, Aji; Apriani, Zenita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Education is an important process in shaping humans to be able to develop knowledge, attitudes, values, and behaviors that support personal and social growth. SMA Negeri 1 Karawang is one of the State Senior High Schools in Karawang Regency which was established on September 16, 1959. This study aims to determine the effect of work motivation and work discipline on teacher performance at SMA Negeri 1 Karawang. The method used is a quantitative descriptive and verification approach with a saturated sampling approach. The research sample consisted of 39 teachers. Multiple linear regression data analysis was carried out using the SPSS version 26 application. The results of the study can be concluded that work motivation with a score of 2,285 and an average of 175.84 is in the very good category and work discipline with a score of 2,333 and an average of 179.46 is in the very good category. Teacher performance with a score of 2,338 and an average of 179.84 is in the very good category. The results of the t-test show that work motivation has a significant value of 0.001 <0.05 and t-count 3.786> t-table 2.026 significantly influences teacher performance. Work discipline has a significant value of 0.014 <0.05 and t-count 2.592> t-table 2.026 significantly influences teacher performance. Simultaneously, work motivation and work discipline have a significant influence on teacher performance with a significant value of 0.000 <0.05 and F-count 39.252> F-table 3.25 significantly influence teacher performance. The coefficient of determination of the magnitude of the influence of Motivation and Work Discipline on teacher performance is 0.686 or 68.6%, while 31.4% is influenced by other variables that were not studied.